1998
DOI: 10.1148/radiology.209.3.9844671
|View full text |Cite
|
Sign up to set email alerts
|

Radio-frequency tissue ablation: effect of pharmacologic modulation of blood flow on coagulation diameter.

Abstract: The coagulation necrosis achieved for a standardized RF application correlates with relative tissue perfusion. Pharmacologic reduction of blood flow during thermally mediated percutaneous ablation may induce greater coagulation necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
93
0
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(105 citation statements)
references
References 0 publications
4
93
0
8
Order By: Relevance
“…Less heat will be conducted from the closest vicinity of the tip compared to the amount of heat conducted from non-coagulated tissue and the coagulated tissue will thus act as thermal insulation (Fig 2a). The latter model is supported by experimental studies of lesions made in liver with a similar temperature control as in this study (Aschoff et al 2001), or with internal cooling of the electrode (Goldberg et al 1998). Increased blood perfusion decreased lesion size in both cases.…”
Section: Discussionsupporting
confidence: 67%
“…Less heat will be conducted from the closest vicinity of the tip compared to the amount of heat conducted from non-coagulated tissue and the coagulated tissue will thus act as thermal insulation (Fig 2a). The latter model is supported by experimental studies of lesions made in liver with a similar temperature control as in this study (Aschoff et al 2001), or with internal cooling of the electrode (Goldberg et al 1998). Increased blood perfusion decreased lesion size in both cases.…”
Section: Discussionsupporting
confidence: 67%
“…Curley et al [14] have used the Pringle method [15] intraoperatively to reduce liver blood flow, by temporarily stopping portal vein and hepatic artery www.wjgnet.com flow, and improving ablation outcomes. Goldberg et al [16] have used vascular agents, such as halothane, vasopressin and adrenaline, to adjust liver blood volume in order to increase ablation area. TACE is one of the major interventional methods for HCC treatment, and when performed before RFA, it can increase therapeutic efficacy as a result of the decreased heat sink effect [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this discrepancy is that hepatic blood flow may have a cooling effect and could thus have influenced the ablative state in the clinical cases. By contrast, ex vivo bovine liver was not perfused with blood flow (17)(18)(19). Previous studies have demonstrated that a reduction in blood supply, such as in transcatheter arterial chemoembolization, results in enlarged ablative volume (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%